La Capilla Real de Palacio en la crisis del Antiguo Régimen: 1808-1820 - Sánchez Belén, Juan A. (Cuadernos de Historia Moderna, 2002)
The enthronement of Jose I, his fall after the defeat of french army and the return of Fernando VII, are events that affected to the Royal Chapel of Palace in same way they had effects on the rest of institutions, lay and ecclesiastical, of the Monarchy. This articule tries, therefore, to analize the repercutions of those facts on structure and functions of the Royal Chapel as on its personel, who oblied by circunstancies were forced to take party facing the effects that such a decision would have on their later careers.